Directing endothelial differentiation of human embryonic stem cells via transduction with an adenoviral vector expressing the VEGF 165 gene - Rufaihah, Abdul Jalil; Haider, Husnain Khawaja; Heng, Boon Chin; Ye, Lei; Toh, Wei Seong; Tian, Xian Feng; Lu, Kai; Sim, Eugene Kwang‐Wei; Cao, Tong (The journal of gene medicine, 2007)
Endothelial progenitors derived from human embryonic stem cells (hESCs) hold much promise in clinical therapy. Conventionally, lineage‐specific differentiation of hESCs is achieved through supplementation of various cytokines and chemical factors within the culture milieu. Nevertheless, this is a highly inefficient approach that is often limited by poor replicability. An alternative is through genetic modulation with recombinant DNA. Hence, this study investigated whether transduction of hESCs with an adenoviral vector expressing the human VEGF 165 gene (Ad‐hVEGF 165 ) can enhance endothelial‐lineage differentiation. The hESCs were induced to form embryoid bodies (EBs) by culturing them within low‐attachment plates for 7 days, and were subsequently trypsinized into single cells, prior to transduction with Ad‐hVEGF 165 . Optimal transduction efficiency with high cell viability was achieved by 4‐h exposure of the differentiating hESCs to viral particles at a ratio of 1 : 500 for three consecutive days. ELISA results showed that Ad‐hVEGF 165 ‐transduced cells secreted human vascular endothelial growth factor (hVEGF) for more than 30 days post‐transduction, peaking on day 8, and the conditioned medium from the transduced cells stimulated extensive proliferation of HUVEC. Real‐time PCR analysis showed positive upregulation of VEGF, Ang‐1, Flt‐1, Tie‐2, CD34, CD31, CD133 and Flk‐1 gene expression in Ad‐hVEGF 165 ‐transduced cells. Additionally, flow cytometric analysis of CD133 cell surface marker revealed an approximately 5‐fold increase in CD133 marker expression in Ad‐hVEGF 165 ‐transduced cells compared to the non‐transduced control. Hence, this study demonstrated that transduction of differentiating hESCs with Ad‐hVEGF 165 facilitated expression of the VEGF transgene, which in turn significantly enhanced endothelial differentiation of hESCs. Copyright © 2007 John Wiley & Sons, Ltd.